Molecules, cells and networks involved in processing olfactory stimuli in the mouse olfactory bulb - Kuner, Thomas; Schaefer, Andreas T. (e-Neuroforum, 2011)
How sensory stimuli are processed by neural networks is a key question of neuroscience. Olfactory conditioning experiments in mice demonstrated that odour processing is fast and stimulus-dependent. Selective genetic perturbation of the inhibitory circuitry in the first relay station of olfactory processing, the olfactory bulb, altered such discrimination times, with increased inhibition accelerating and decreased inhibition slowing down odour discrimination. This illustrates that inhibition fulfils a key role in sensory processing.
Elektronische Reproduktion der Druckausgabe
Gesehen am 11.07.2022